A long-term follow-up of a case of Rogers syndrome, Thiamine responsive megaloblastic anemia - Chaware, Shriya; Jahagirdar, Rahul; Deshpande, Ruma; Bafna, Vibha (International Journal of Contemporary Pediatrics, 2023)
Thiamine-responsive megaloblastic anemia (TRMA) also known as Rogers syndrome is a rare autosomal recessive disorder characterized by megaloblastic anemia, diabetes mellitus, and progressive sensorineural deafness. The disease can be manifested anytime between infancy and adolescence, and all the cardinal findings may not be present at the time of the diagnosis. The main defect lies in the active thiamine uptake into cells which is disturbed. Not many cases have been reported about the long-term follow-up of children with this disorder and their associated complications. We hereby report a 14 years follow-up of a girl with Rogers syndrome diagnosed at toddler age with nonresponsive anemia and diabetes and further progressed to have sensorineural hearing loss. Her clinical exome study showed a mutation in the SLC19A2 gene. This experience illustrates the relevance of a detailed evaluation and regular follow-up to assess the progression of the syndrome till her pubertal age.